NILAI-NILAI PENDIDIKAN KARAKTER DALAM QUR’AN SURAH LUQMAN AYAT 12-19 DAN PEMILIHAN MODEL-MODEL PEMBELAJARAN APLIKATIF YANG RELEVAN TERHADAP PEMBENTUKAN AKHLAK SISWA - Saopiati; Khaeruddin; Hidayati, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the character education values contained in Qur'an Surah Luqman verses 12–19 and identifies applicable learning models that are relevant to strengthening students' moral character. The research was motivated by the increasing phenomenon of moral degradation among students in the era of globalization, which demands a character education approach based on Islamic values derived from the Qur'an. This study employed a qualitative approach using library research with a thematic interpretation (tafsir maudhu'i) method. Primary data were obtained from the Qur'anic verses and several authoritative tafsir references, including Tafsir Al-Misbah, Tafsir Ibn Kathir, Tafsir Al-Munir, Tafsir Jalalain, and Tafsir of the Ministry of Religious Affairs of the Republic of Indonesia. The collected data were analyzed through content analysis to identify the main character values and formulate relevant instructional models. The findings reveal seven major character education values, namely gratitude, monotheism (tawhid), filial piety (birr al-walidayn), awareness of Allah's supervision (muraqabatullah), worship combined with enjoining good and forbidding evil, patience, humility, simplicity, and politeness. These values can be integrated into Islamic Religious Education through contextual learning models such as Value Clarification Technique, Problem-Based Learning, Cooperative Learning, Project-Based Learning, Role Playing, Habituation, and Exemplary Learning. The study concludes that integrating Qur'anic character values with appropriate learning models can effectively support the development of students' moral character in both classroom learning and everyday life.